1996
DOI: 10.1136/jech.50.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Desire for the body normal: body image and discrepancies between self reported and measured height and weight in a British population.

Abstract: Conclusions: The association between geographical area and cervical cancer persists after controlling for 10 other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
1
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 3 publications
5
82
1
3
Order By: Relevance
“…A recent British study found that 27% of men and 10% of women who were overweight described their weight as about right, and 12% of men and 37% of women whose weight was normal' considered themselves to be too heavy. 9 Similar ®ndings have also been reported in an Australian study. Paxton and colleagues 10 found that 17% of men and 6% of women in the overweight or obese range (BMI b 25) classi®ed themselves as a good weight, and 24% of men and 47% of women in the acceptable weight range considered themselves to be at least slightly overweight.…”
Section: Introductionsupporting
confidence: 83%
“…A recent British study found that 27% of men and 10% of women who were overweight described their weight as about right, and 12% of men and 37% of women whose weight was normal' considered themselves to be too heavy. 9 Similar ®ndings have also been reported in an Australian study. Paxton and colleagues 10 found that 17% of men and 6% of women in the overweight or obese range (BMI b 25) classi®ed themselves as a good weight, and 24% of men and 47% of women in the acceptable weight range considered themselves to be at least slightly overweight.…”
Section: Introductionsupporting
confidence: 83%
“…10 Although there is a tendency to overestimate height and underestimate weight in surveys where these are self-reported, 11 resulting in an underestimate of BMI, this is unlikely to account for the large differences noted. We suggest that the relatively low mean BMI is largely attributable to the skewed social class distribution of the cohort and the generally health conscious nature of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]5,18,22,23 Explanations for the absence of such associations are unclear, particularly as participants' behaviours and levels of adiposity were in line with UK population estimates, the social class distribution of the cohort was reasonable and substantial differences were not found between those who attended and those who did not attend a clinic session.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the accuracy of self-reported data may vary with body size, age, sex and social position. [1][2][3][4][5][6] Although overweight subjects tend to under-report their weight to a greater extent than those who are lean, mis-reporting occurs across all levels of body size. This suggests that 'figure consciousness' rather than body size per se may also be a source of bias.…”
Section: Introductionmentioning
confidence: 99%